The Basic and Relational Meaning of the Word Hadith in the Qur’an: A Semantic Study by Toshihiko Izutsu - Syaikhu, Ahmad; Alfain, Bihevi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study explores the meaning of the word ḥadīṡ in the Qur’an using Toshihiko Izutsu’s semantic theory, which focuses on uncovering the meaning of words in the Qur’an through the analysis of basic and relational meanings. The word ḥadīṡ appears in the Qur’an 23 times, falling into four categories: ḥadīṡan, ḥadīṡin, al-ḥadīṡi, and ḥadīṡu. This research employs a descriptive qualitative method, and the data collection technique used is observation with note-taking as a follow-up technique. The study finds that, based on relational meaning analysis in the syntagmatic dimension, the word ḥadīṡ in the Qur’an carries various meanings depending on its context. Furthermore, in the paradigmatic analysis, ḥadīṡ is found to be synonymous with the words qaul, khabar, kalām, qiṣṣaṣ, and naba’, and antonymous with the word qadīm.